2013
DOI: 10.1016/j.surfcoat.2013.06.050
|View full text |Cite
|
Sign up to set email alerts
|

High quality graphene synthesized by atmospheric pressure CVD on copper foil

Abstract: International audienceGraphene was synthesized at 1000 °C by Atmospheric Pressure Chemical Vapor Deposition on copper foil from methane diluted in argon and hydrogen. The influence of the main synthesis parameters was studied on 2 × 2 cm2 foils in order to obtain continuous monolayer graphenewithout crystalline defect. The uniformity, crystal quality and number of layers of graphenewere analyzed by Raman spectroscopy and Scanning Electronic Microscopy. First, an increase of the annealing pre-treatment duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
0
17
1
Order By: Relevance
“…Thus, increasing the CH 4 partial pressure has no effect on the nucleation density past the supersaturation point. However, if the CH 4 partial pressure is too high, bilayer and multilayer graphene may form [36]. Thus, a certain parameter exists for graphene growth on Cu substrates to be self-limiting, which seems to be closely related to the partial pressure of CH 4 .…”
Section: Gas Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, increasing the CH 4 partial pressure has no effect on the nucleation density past the supersaturation point. However, if the CH 4 partial pressure is too high, bilayer and multilayer graphene may form [36]. Thus, a certain parameter exists for graphene growth on Cu substrates to be self-limiting, which seems to be closely related to the partial pressure of CH 4 .…”
Section: Gas Ratiomentioning
confidence: 99%
“…As mentioned in Section 2, graphene has a tendency to nucleate at defect sites such as the grain boundaries of Cu and other impurity sites. Because long-term annealing at elevated temperatures promotes grain growth and the recrystallization of the Cu substrate, it reduces the number of possible nucleation sites for graphene [36,46]. Wang et al [46] clearly showed that, by increasing the pregrowth annealing time from 1 h to 3 h, the nucleation density of graphene was reduced, which in turn led to an increase in the graphene domain size.…”
Section: Substrate Pretreatmentmentioning
confidence: 99%
“…These characteristics mean that the broader application of graphene has attracted great interest [1][2][3][4][5][6][7]. Perfect graphene is a two-dimensional crystal composed of carbon atoms, as shown in Figure 1, in which the atoms are arranged in a honeycomb hexagon, and if they form in pentagons or heptagons then these constitute defects.…”
Section: Introductionmentioning
confidence: 99%
“…However, mechanically exfoliating graphene from bulk graphite is not suitable for the synthesis of large surface area devices, nor for use in practical device fabrication processes. In contrast, chemical vapor deposition (CVD) is can be used with large surface area applications and has a relatively low cost [4,[7][8][9][10]. The low pressure CVD (LP-CVD) method of growing graphene on a Cu substrate has been widely reported in the literature, there are many studies on the mechanism of the resulting materials [3,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A relatively simple and quite effective way to create such a substrate is to coat a common transparent plane material with a thin layer of graphene [1]. Plane graphene layers on substrates were already synthesized by several groups, mainly on copper, nickel and silicon carbide [2][3][4][5]. Also it has been shown already that vertically oriented graphene layers, so-called few-layer graphene (FLG) sheets with a thickness <1-5 nm or carbon nanowalls (CNWs) with a larger thickness of >5 nm, can be synthesized on substrates.…”
Section: Introductionmentioning
confidence: 99%